(untitled) - Bloomberg, Jason (Hoboken, N.J., 2006)
The real value of this book is that it makes SOA and Web services, which are critical and business-transforming, crystal-clear to the layman, both business and IT leaders. The book stays focused on the real-world issues facing business and government institutions today. In an industry full of experts of many stripes, Ron and Jason are the real thing: savvy, experienced, and realistic.
Keywords: Management information systems,Quản trị hệ thống thông tin